Assessment Model in Indonesian Language Learning Based on The Merdeka Curriculum at Junior High School in Banyuwangi Regency - Megawati Megawati; Imam Suyitno; Titik Harsiati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to describe the types, forms, functions, and assessment techniques of Indonesian teachers based on the Merdeka Curriculum, as well as the obstacles encountered in its implementation. This study used a descriptive method with a qualitative approach. The research was carried out across six junior high schools within the Banyuwangi Regency. The participants of this study were Indonesian junior high school teachers. Information was gathered from primary and secondary sources. Primary data stemmed from observations and interviews, whereas secondary data encompassed assessment-related documents. Data analysis was performed using Milles and Huberman flow analysis techniques in three steps: data reduction, data presentation, and drawing conclusions. The findings of the research reveal the existence of two distinct assessment approaches in Indonesian language education within Banyuwangi Regency's junior high schools: formative assessment and summative assessment. Formative assessments included those at the beginning and during learning. Most teachers use written test techniques to diagnose students' cognition using the rubric as an instrument. Meanwhile, the teacher used questionnaires, interviews, and observations to diagnose students' noncognition. Formative assessment during learning is conducted using a variety of techniques and instruments adapted to the achievement elements of learning in Indonesian language. Summative assessments were carried out by the majority of teachers at the end of each chapter, midterm, and end of the semester using a written test technique. This research has implications for school stakeholders, teachers, and future researchers.